PENGARUH PREFERENSI MEDIA SOSIAL, MOTIVASI BELAJAR, DAN SELF-EFFICACY TERHADAP NIAT STUDI LANJUT SISWA KELAS XI JURUSAN AKUNTANSI SMK NEGERI DI JAKARTA PUSAT - Nur Maulidiya; Santi Susanti; Agus Wibowo (Qalam : Jurnal Ilmu Kependidikan, 2026)
The decision of vocational high school students to pursue higher education is influenced by various external and internal factors. This study aimed to examine the effects of social media preference, learning motivation, and self-efficacy on the intention to pursue higher education among eleventh-grade accounting students in public vocational schools in Central Jakarta. A quantitative survey method was employed involving students from three public vocational schools selected using proportional random sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics. The findings revealed that social media preference, learning motivation, and self-efficacy each had a positive and significant influence on students' intention to pursue higher education. Simultaneously, the three independent variables also significantly affected students' intention to continue their studies. These findings indicate that appropriate use of social media, strong learning motivation, and high self-efficacy can strengthen vocational students' intention to continue their education at the university level.